2002
DOI: 10.1021/jo025962y
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Synthesis of Phenanthrenes by a PtCl2-Catalyzed Cycloisomerization Reaction

Abstract: Readily available biphenyl derivatives containing an alkyne unit at one of their ortho positions are converted into substituted phenanthrenes upon exposure to catalytic amounts of either PtCl(2), AuCl(3), GaCl(3), or InCl(3) in toluene. This 6-endo-dig cyclization likely proceeds through initial pi-coordination of the alkyne unit followed by interception of the resulting eta(2)-metal complex by the adjacent arene ring. The reaction is inherently modular, allowing for substantial structural variations and for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
164
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(170 citation statements)
references
References 27 publications
4
164
0
2
Order By: Relevance
“…Carbon-carbon bond formation has also been accomplished utilizing a hydroarylation reaction (Figure 3d). 43 It is important to note that all reactions are catalyzed by Pt NPs in yields comparable to, if not slightly better than those obtained with homogeneous PtCl 2 . Furthermore, in the case of the cyclization of compound 9, our NP catalysts show selectivity favoring the para-isomer 10 over the ortho-isomer, nearly equivalent to that observed in homogeneous PtCl 2 systems.…”
mentioning
confidence: 75%
“…Carbon-carbon bond formation has also been accomplished utilizing a hydroarylation reaction (Figure 3d). 43 It is important to note that all reactions are catalyzed by Pt NPs in yields comparable to, if not slightly better than those obtained with homogeneous PtCl 2 . Furthermore, in the case of the cyclization of compound 9, our NP catalysts show selectivity favoring the para-isomer 10 over the ortho-isomer, nearly equivalent to that observed in homogeneous PtCl 2 systems.…”
mentioning
confidence: 75%
“…Fürstner et al reported a similar reaction for the synthesis of phenanthrenes that is catalyzed by PtCl 2 or other metal halides, such as AuCl 3 , GaCl 3 , and InCl 3 . [12] Sames et al developed a PtCl 4 -catalyzed intramolecular hydroarylation under mild conditions for the synthesis of chromenes, 1,2-dihydroquinolines, and coumarins.…”
Section: Introductionmentioning
confidence: 99%
“…[14] Importantly, metal vinylidene intermediates [19,20] are not involved in these cyclizations, as shown by deuteration experiments [21] and by the fact that internal alkynes are also cyclized with electrophilic metal complexes. [12] Although the mechanistic hypothesis shown in Scheme 1 is plausible and is inspired by a fundamental mechanism in organic chemistry, an alternative explanation based on the formation of metal cyclopropyl carbenes could also account for the experimental results. Indeed, we have shown that the Pt II -catalyzed reaction of furans with alkynes proceeds via metal cyclopropyl carbenes, [21,22,23] similar to those involved in the alkoxycyclization and skeletal rearrangement of enynes.…”
Section: Introductionmentioning
confidence: 99%
“…h) 2-Haloalkynyl-biphenyls are cyclized to 9-halophenanthrenes upon reaction with AuCl in boiling toluene [124].…”
Section: Activation Of Aucl With Solvents Nitrogen Donors and Reductmentioning
confidence: 99%